An ultrafast performance regeneration of aged stainless steel by pulsed electric current. (August 2018) - Liu, Xuebing; Zhang, Xinfang
Abstract: It has been proved thermodynamically that the dissolution of the precipitates is directly related to the temperature, that is, if the critical temperature cannot be reached, the precipitates can only grow and the precipitation process continues. Therefore, the reverse thermodynamic dissolution behavior of the precipitates under certain conditions will become very significant. Here we provide a new pathway to investigate the dissolution behavior of highly thermally stable precipitates under electropulsing. Our findings show that the change of free energy caused by the difference in electrical conductivities between the precipitates and matrix leads to the inverse thermodynamic precipitates' dissolution. Graphical abstract: Unlabelled Image